Homer Simpson Goes to Washington : American Politics through Popular Culture - Schultz, Stanley K.; Foy, Joseph J. (Book collections on Project MUSE., 2008)
The modern landscape of American entertainment is filled with commentary on the state of the union. Viewers turn to The Daily Show instead of Fox or CNN, satirical films such as Wag the Dog, cartoons like The Simpsons, or controversial action dramas similar to 24 in order to learn more about current events in the United States. Popular culture is educating America more than the nightly news, aiding viewers in their quest to understand the American political system. In Homer Simpson Goes to Washington: American Politics through Popular Culture, Joseph J. Foy and other contributing scholars.